Periodic and the Educational Paradigm of Ibnu Sina - Abdullah Muwaffaq (EduLine: Journal of Education and Learning Innovation, 2022)
Avicenna is one of the figures who has made a major contribution to the body of knowledge in Islam, especially about Islamic education. This paper discusses the educational paradigm of Ibn Sina. In general, education is an appropriate and strategic means and effort to save human life from any matter. The synthesis of Ibn Sina's thought that "education is the art of making man moral", namely education makes life by the goals of society that are big and good. Philosophically, education is an investment in the future of human life that will change one's mindset, paradigm, character, and even fate and profession as a result of a series of processes of transfer of knowledge, transfer of value, and transfer of skills. Besides that, Ibn Sina's thoughts regarding education in a structured way from goals, curriculum, learning methods, and teachers or educators are factors rather than determinant elements in education. Therefore, Ibn Sina's thoughts can be used as an important reference in advancing the world of education. In another view, the results of Ibn Sina's thoughts are nothing but his life experience in discovering a very broad knowledge which was then poured into written media and became the primary source of knowledge in his time. In this regard, the study that has been presented is one of the assumptions of exploring these primary sources from the scientific treasures of Ibn Sina